CLINICAL PHENOMENOLOGY OF TIC DISORDERS IN CHILDREN: A SERIES OF CLINICAL CASES - Nurmatova D.A., Shomansurov Sh.Sh.,; Sayfitdinkhuzhaev Z.F.,; Okhunbaev J.M., (Central Asian Journal of Medicine, 2025)
TIC disorders in children are a common neurological pathology, ranging from transient benign forms to chronic and disabling ones, such as Gilles de la Tourette syndrome (CJT). The article presents three typical clinical cases reflecting the spectrum of tic hyperkinesis: Transient tics in a 7-year-old child with complete regression on the background of non-drug correction. Chronic motor tics in a 9-year-old girl who required a combination of cognitive behavioral therapy and pharmacotherapy. Gilles de la Tourette syndrome in a 12-year-old boy with comorbid psychiatric disorders, demonstrating the need for a multidisciplinary approach. Special attention is paid to differential diagnosis, the role of stress factors, as well as modern treatment methods, including behavioral techniques (habit reversal training), pharmacotherapy (clonidine, risperidone) and psychosocial support. The importance of early intervention to improve the prognosis and quality of life of patients is emphasized.